Lameness associated with tarsal haemarthrosis as the sole clinical sign of idiopathic immune-mediated thrombocytopenia in a dog - Walton, M. B.; Mardell, E.; Spoor, M.; Innes, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
A four-year-old, male Cocker Spaniel was presented for investigation of pelvic limb stiffness. There was palpable effusion of both tarsi, and analysis of synovial fluid from these joints indicated previous haemorrhage. After further investigation a diagnosis of idiopathic immune-mediated thrombocytopenia was made. The dog responded to treatment with prednisolone and azathioprine. To the authors’ knowledge, this is the first reported case of confirmed haemarthrosis as the sole presenting clinical sign for canine idiopathic immunemediated thrombocytopenia.
Keywords: Haemarthrosis; idiopathic immunemediated thrombocytopenia; lameness